Some results on the Pv,2nPv,2n, Kv,nKv,n, and Hv,nHv,n-integral transforms - (:unkn) unknown (My University, 2017)
0

In this paper, the authors consider the Pv,2n -transform, the Gn -transform, and the Kv,n -transform as generalizations of the Widder potential transform, the Glasser transform, and the Kv -transform, respectively. Many identities involving these transforms are given. A number of new Parseval Goldstein type identities are obtained for these and many other well-known integral transforms. Some useful corollaries for evaluating infinite integrals of special functions are presented. Illustrative examples are given for the results.
Keywords: Matematik